ANALISIS PENGARUH LIKUIDITAS, STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP PRICE EARNING RATIO (STUDI EMPIRIS PADA SAHAM-SAHAM BLUE CHIPS YANG TERDAFTAR DI BEI TAHUN 2010-2014) - admin, Gabriella Sinlia B11112003 (Jurnal Manajemen Update, 2017)
This research aims to examine the influence of liquidity, capital structure, dividend policy, and firm size to Price Earning Ratio on blue chips stocks listed in Indonesia Stock Exchange for the period of 2010-2014.  Independent variables used are liquidity, capital structure, dividend policy, and firm size.  Dependent variable used is Price Earning Ratio. This is a quantitative research.  The population of this research are the blue chips stocks listed in Indonesia Stock Exchange.  The sample is taken by purposive sampling method, therefore there are 12 companies for the 5 years research period.  Analysis technique used is multiple linear regression conducted by SPSS 18.0. The results of the research show that liquidity has no significant influence with a negative coefficient to Price Earning Ratio, capital structure has significant influence with a positive coefficient to Price Earning Ratio, dividend policy has no significant influence with a negative coefficient to Price Earning Ratio and firm size has significant influence with a negative coefficient to Price Earning Ratio.  The ability of these four variable to explain the influence of themselves towards Price Earning Ratio as shown by Adjusted R Square is 14,8% while the remaining 85,2% is influenced by other factors not included in this research. Keywords : Price Earning Ratio, Liquidity, Capital Structure, Dividend Policy, Firm Size.